(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This study investigated how the indigenous legends presented by Boi Caprichoso at the Parintins Festival (2023 and 2024) constitute pedagogical practices. Using a qualitative approach, it analyzed Ypuré: the Lady of Greed and The Creation of the Night through documentary and audiovisual records and semi-structured interviews. The findings indicate that these narratives promote a visual, sound, and spiritual pedagogy that values orality, nature, and Indigenous spirituality, concluding that the performing arts are capable of renewing myths as educational tools.